Facile Patterning of Laser‐Induced Graphene with Tailored Li Nucleation Kinetics for Stable Lithium‐Metal Batteries. Issue 38 (20th August 2019) - Yi, Jingsi; Chen, Jiahua; Yang, Zheng; Dai, Yang; Li, Weimin; Cui, Jiang; Ciucci, Francesco; Lu, Ziheng; Yang, Chunlei
Abstract: A facile and scalable approach is reported to stabilize the lithium‐metal anode by regulating the Li nucleation and deposition kinetics with laser‐induced graphene (LIG). By processing polyimide (PI) films on copper foils with a laser, a 3D‐hierarchical composite material is constructed, consisting of a highly conductive copper substrate, a pillared array of flexible PI, and most importantly, porous LIG on the walls of the PI pillars. The high number of defects and heteroatoms present in LIG significantly lowers the Li nucleation barrier compared to the copper foil. An overpotential‐free Li nucleation process is identified at current densities lower than 0.2 mA cm −2 . Theoretical computations reveal that the defects serve as nucleation centers during the heterogeneous nucleation of lithium. By adopting such composites, ultrastable lithium‐metal anodes are obtained with high Coulombic efficiencies of ≈99%. Full lithium‐metal cells based on LiFePO4 cathodes with a material loading of ≈15 mg cm −2 and a negative/positive ratio of 5/1 could be cycled over 250 times with a capacity loss of less than 10%. The current work highlights the importance of nucleation kinetics on the stability of metallic anodes and demonstrates a practical method toward long lasting Li‐metal batteries. Abstract : Laser processing is investigated as a scalable approach to fabricate laser‐induced‐graphene (LIG) as a stable lithium host. The highly defective and heterodoping nature of LIG leads to a significantly lowered lithium nucleation barrier. An anomalous overpotential‐free nucleation process is observed at low current densities. Density functional theory calculations are carried out to reveal the effect of defects on lithium nucleation.